Implementasi Kurikulum Merdeka Belajar dalam Meningkatkan Hasil Belajar PPKn Kelas X ATPH di Sekolah SMK Negeri 1 Bulango Utara Kabupaten Bone Bolango - Cindra Maulana; Sukarman Kamuli; Yuli Adhani (Badan Penerbit STIEPARI Press, 2025)
This study aims to discuss the implementation of the Independent Learning Curriculum in improving PPKn learning outcomes for Class X ATPH at SMK Negeri 1 Bulango Utara. The study used qualitative research with a descriptive approach with data obtained through observation, interviews and documentation for the validity of the data obtained. While primary data comes from teachers and students, and secondary data through school archives. The results of the study show that the implementation of the Independent Learning Curriculum in improving PPKn learning outcomes in schools can be from the application of the Pancasila Student Profile Project which consists of four dimensions, namely, faith, devotion to God Almighty, mutual cooperation, independence and creativity. Meanwhile, the obstacles faced in its implementation are the readiness of teachers and limited learning facilities so that they affect the learning process.